2021
DOI: 10.1016/j.jmig.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Bartholin's Gland Abscess: Is Word Catheter Superior to Marsupialization?

Abstract: Study Objective: Bartholin's gland abscess may occur in up to 2% of the women. Surgical drainage using the Word catheter application or marsupialization is the treatment of choice in the management of Bartholin's gland abscess. We aimed to compare the abscess recurrence rates between these 2 surgical methods. Design: A retrospective cohort database study. Setting: A university-affiliated, high-volume teaching hospital in southern Israel. Patients: All women who were surgically treated for Bartholin's gland abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In a retrospective cohort study, Karsbük et al concluded that the Word catheter group had higher recurrence rates and dissatisfaction levels, with the only advantage being its shorter operation time (16). On the contrary, Rotem et al conducted a retrospective cohort database study and reported no differences in clinical and microbiological features, recurrence rates, recurrent admissions or postoperative complications between patients treated with Word catheters and those receiving marsupialization (17). Kroese et al initiated a multicenter, open-label, randomized controlled trial and highlighted that in women with an abscess or cyst of the Bartholin gland, treatment with Word catheter and marsupialization resulted in comparable recurrence rates (18).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study, Karsbük et al concluded that the Word catheter group had higher recurrence rates and dissatisfaction levels, with the only advantage being its shorter operation time (16). On the contrary, Rotem et al conducted a retrospective cohort database study and reported no differences in clinical and microbiological features, recurrence rates, recurrent admissions or postoperative complications between patients treated with Word catheters and those receiving marsupialization (17). Kroese et al initiated a multicenter, open-label, randomized controlled trial and highlighted that in women with an abscess or cyst of the Bartholin gland, treatment with Word catheter and marsupialization resulted in comparable recurrence rates (18).…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy regarding the best treatment of a Bartholin’s cyst[ 4 , 6 , 30 ]. I&D, fistulization with a Word catheter, marsupialization, and excision of the cyst are all commonly performed procedures[ 31 , 32 ]. I&D is the simplest way to treat Bartholin’s cyst, and it has the shortest recovery time due to its simplicity.…”
Section: Discussionmentioning
confidence: 99%
“…But there was only limited evidence in this systematic review[ 6 ]. Among these interventions, fistulization with a Word catheter and marsupialization are the two most commonly applied procedures[ 31 , 33 ]. Previous studies reported that both interventions had comparable recurrence rates[ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations